Selected problems of the labour market as approached by Keynes, Galbraith and Friedman - Zagóra-Jonszta, Urszula (Wybrane problemy rynku pracy w ujęciu Keynesa, Galbraitha i Friedmana, 2019)
The paper discusses the selected dilemmas of the labour market as approached by three great economists of the 20th century – Keynes, Galbraith and Friedman. Each of them represented a different trend in economics. Keynes was the creator of the so-called Keynesianism, Galbraith represented neo-institutionalism and Friedman formulated the theory of monetarism. Although they all considered unemployment to be an undesirable phenomenon, they were different in their approaches to combating it. The differences in views resulted from doctrinal reasons. Keynes proposed various forms of counteracting unemployment based on the active involvement of the state, Galbraith mainly focused on an adequate social policy, whereas Friedman believed that only a free market can improve the situation on the labour market, and negated all governmental support programs. The aim of the paper is to compare the attitudes of the discussed economists towards the selected problems of labour market, mainly on the basis of their publications. The study applies the method of source analysis as well as descriptive and comparative methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 172-183
Keywords: Keynes; Galbraith; Friedman; rynek pracy; labour market